2022
DOI: 10.1108/jima-09-2021-0309
|View full text |Cite
|
Sign up to set email alerts
|

Brand attributes, corporate brand image and customer loyalty of Islamic banks in Malaysia

Abstract: Purpose The purpose of this study is to empirically examine the antecedents and consequences of corporate brand image in the context of Islamic banks in Malaysia. The antecedents of corporate brand image are divided into three categories which are functional brand attribute, emotional brand attribute and spiritual brand attribute. The consequence of corporate brand image on the other hand is loyalty. Design/methodology/approach A self-administered survey was used to collect data from experienced Islamic bank… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 97 publications
0
10
0
Order By: Relevance
“…The main theoretical contribution of this study is the comparison of traditional banks and fintechs through an unprecedented model that relates dimensions of perceived value by Brazilian retail banking customers (Paiva et al ., 2009) with satisfaction (Larán and Rossi, 2003) and loyalty (Murad and Torres, 2008). It was found that there is a real potential to add new perspectives to the field of research, considering previous studies that deal with determining factors of satisfaction and loyalty of consumers of financial services (Gallarza et al ., 2016; Oni et al ., 2016; Chuah et al ., 2017; Milan et al ., 2018; Jünger and Mietzner, 2020; Raza et al ., 2020; Singh et al ., 2020; Boot et al ., 2021; Wang et al ., 2021; Khan et al ., 2022; Ab Hamid et al ., 2022). In addition, this study made it possible to highlight specific dimensions of the value perceived by consumers of financial services that can interfere with satisfaction and loyalty, whether for traditional banks or fintechs.…”
Section: Discussionmentioning
confidence: 99%
“…The main theoretical contribution of this study is the comparison of traditional banks and fintechs through an unprecedented model that relates dimensions of perceived value by Brazilian retail banking customers (Paiva et al ., 2009) with satisfaction (Larán and Rossi, 2003) and loyalty (Murad and Torres, 2008). It was found that there is a real potential to add new perspectives to the field of research, considering previous studies that deal with determining factors of satisfaction and loyalty of consumers of financial services (Gallarza et al ., 2016; Oni et al ., 2016; Chuah et al ., 2017; Milan et al ., 2018; Jünger and Mietzner, 2020; Raza et al ., 2020; Singh et al ., 2020; Boot et al ., 2021; Wang et al ., 2021; Khan et al ., 2022; Ab Hamid et al ., 2022). In addition, this study made it possible to highlight specific dimensions of the value perceived by consumers of financial services that can interfere with satisfaction and loyalty, whether for traditional banks or fintechs.…”
Section: Discussionmentioning
confidence: 99%
“…Social identity theory examines the role of religiosity in driving consumer preference for IBs (Junaidi et al , 2022b), and commitment theories elaborate on the role of consumer ego in driving word of mouth (Sumaedi et al , 2015). Gestalt psychology theory is applied to study the effect of corporate brand image on consumer–IB relationships (Ab Hamid et al , 2022). Furthermore, the triangular theory of love and expectation-confirmation theory specifically addresses consumer–IB relationships (Ismail, 2022).…”
Section: Theory-context-characteristics-methods Frameworkmentioning
confidence: 99%
“…The other consumer-related variables in this category that have received attention are attitude (Sen et al , 2020), perception (Riaz et al , 2017), choice behavior (Amin et al , 2022; ElMassah and Abou-El-Sood, 2022) and intention (Maryam et al , 2022; Panggi et al , 2022; Samsudeen et al , 2022). Consumer loyalty is the other research stream with significant attention (Abdul Hadi and Muwazir, 2021; Ab Hamid et al , 2022; Saiti et al , 2022; Tegambwage and Kasoga, 2023). The measures related to the IB-specific factor of religiosity are largely considered as an independent variable than as a dependent variable (Abou-Youssef et al , 2015).…”
Section: Theory-context-characteristics-methods Frameworkmentioning
confidence: 99%
“…Religiosity or religious commitment is the degree to which a person adheres to religious values, beliefs, and practices and applies them in daily life [ 79 ]. Religion affects human behavior and attitudes [ 80 , 81 ]. Religiosity plays a dominant and influential role in Muslim consumers’ attitudes in Bangladesh [ 82 ] and UAE [ 83 ].…”
Section: Literature Reviewmentioning
confidence: 99%